2017
DOI: 10.1021/acs.jpcc.7b04806
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Polycitydylic Acid to Graphene Oxide: Spectroscopic Study and Computer Modeling

Abstract: Hybridization of nucleic acids with graphene nanomaterials is of great interest due to its potential application in genosensing and nanomedicine. In this work we study the interaction between polyribocytidylic acid (poly­(rC)) and graphene oxide (GO). The study involves comparing the UV absorption spectra of the free polymer and the polymer bonded to graphene oxide and analyzing the vibrational structure of the systems and their components using FTIR spectroscopy. Spectral shifts of the electronic and vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Note that the ultrasound action used in these experiments for preparation of GO aqueous suspensions does not lead to the quantity increase of oxygen-containing groups. Our previous analysis of the size of the GO akes in water suspension prepared by similar method [17] showed that we obtained mainly single layers or bilayers of GO with a lateral size ranging from 0.5 to 2 μm (the average ake size is about 1 μm).…”
Section: Go Characterization By Ftir Spectroscopymentioning
confidence: 71%
See 2 more Smart Citations
“…Note that the ultrasound action used in these experiments for preparation of GO aqueous suspensions does not lead to the quantity increase of oxygen-containing groups. Our previous analysis of the size of the GO akes in water suspension prepared by similar method [17] showed that we obtained mainly single layers or bilayers of GO with a lateral size ranging from 0.5 to 2 μm (the average ake size is about 1 μm).…”
Section: Go Characterization By Ftir Spectroscopymentioning
confidence: 71%
“…For more detailed analysis of content of oxygen-containing groups in the GO structure, which may in uence the ESR spectra, the FTIR spectroscopy was exploited. Up to now, the main characteristic absorption bands, which allow unique identi cation of GO, are known [16,17]. In accordance with this assignment, the GO absorption bands of the IR spectrum in the range of 1750-1600 cm −1 are attributed to stretch vibrations of ](C O) mainly of the carbonyl and carboxylic groups ( Figure 3), and the bands in the range of 1600-1500 cm −1 are assigned to stretch vibrations of ](C S) involving fragments of the sp 2hybridized graphene domains.…”
Section: Go Characterization By Ftir Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…. In recent years several researchers have investigated the adsorption phenomenon of biomolecules on GO surface …”
Section: Methodsmentioning
confidence: 99%
“…[11] Nowadays, GO has been utilized with great interest in the field of near-infrared photothermal treatment of cancer, Alzheimer diseases etc.. [12][13][14] In recent years several researchers have investigated the adsorption phenomenon of biomolecules on GO surface. [6,[15][16] It is deeply-rooted that fluorescence of the organic fluorophore, [17,18] and biomolecules [19,20] were quenched in the presence of graphene oxide. Electron transfer, fluorescence resonance energy transfer (FRET), non-radiative dipole-dipole interaction are commonly responsible for this quenching phenomena.…”
mentioning
confidence: 99%